Electrochemical Study on the Interaction between the {2-[2-Hydroxy-5-sulfobenzylidene) amino]acetylamino}acetic Copper(II) Complex and DNA - Jie, G.F.; Sheng Zhang, Shu; Li, Y.; Jiao, K.; Yang, F. (Asian Journal of Chemistry, 2010)
A voltamrnetric study of the interaction between CuL (L = {2-(2-hydroxy-5-Sulfobenzylidene)amino] acetylamino}acetic acid) and DNA at glassy carbon electrode in 0.1 mol L-1, pH 6.90, Na2HPO4-NaH2PO4 buffer solution is described. After adding DNA to CuL solution, the oxidation peak of CuL decreases. The oxidation peak potential of CuL in a pH 6.90 phosphate buffer solution in the presence of DNA shifts negatively, which indicates that the binding mode of CuL to DNA is electrostatic binding. Experimental results indicate that CuL can bind to DNA to form a 1: 1 association complex with the binding constant of 7.45 x 104 mol-1 L.